2022
DOI: 10.3390/math10132181
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting Selected Colombian Shares Using a Hybrid ARIMA-SVR Model

Abstract: Forecasting future values of Colombian companies traded on the New York Stock Exchange is a daily challenge for investors, due to these stocks’ high volatility. There are several forecasting models for forecasting time series data, such as the autoregressive integrated moving average (ARIMA) model, which has been considered the most-used regression model in time series prediction for the last four decades, although the ARIMA model cannot estimate non-linear regression behavior caused by high volatility in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 43 publications
0
20
0
Order By: Relevance
“…The linear regression-based ARIMA method does better using linear information, whereas the non-linear, elevated LSTM approach does effectively use share price time sequence information. [18] In latest days, period sequence research has shown that Long Short-term Memories (LSTM), an advancement of Recurring Neuronal Networks (RNN), performs effectively [17]. Because LSTM seems to have the property of growing as the cycle of events, the drawbacks of gradients vanishing and slope inflation inside the RNN models could be eliminated throughout the LSTM trained procedure of extended periods [15].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The linear regression-based ARIMA method does better using linear information, whereas the non-linear, elevated LSTM approach does effectively use share price time sequence information. [18] In latest days, period sequence research has shown that Long Short-term Memories (LSTM), an advancement of Recurring Neuronal Networks (RNN), performs effectively [17]. Because LSTM seems to have the property of growing as the cycle of events, the drawbacks of gradients vanishing and slope inflation inside the RNN models could be eliminated throughout the LSTM trained procedure of extended periods [15].…”
Section: Discussionmentioning
confidence: 99%
“…Overall precision of LSTM approach could surpass that of the ARIMA framework. The LSTM framework provides the highest precision when predicting the following day's share value, as per research by Lu et al who used a variety of algorithms to predict share values [18]. In contrast to LSTM, ARIMA involves a collection of characteristics (p, q, and d) that should be determined using information [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, some studies have constructed forecasting models that combine two or more models. Rubio et al [7] proposed a hybrid model combining an ARIMA and support vector regression to forecast stock prices. Güven et al [8] developed a hybrid model that combined neural networks and support vector regression to forecast sales in the apparel industry.…”
Section: Research On General Demand Forecastsmentioning
confidence: 99%
“…Demand for bento is represented as a time series of sales-data. In research on demand forecasting for timeseries data, many methods have been proposed using statistical models and machine learning [2,3,4,5,6,7,8,9,10,11]. However, few studies have conducted demand forecasting to account for product popularity.…”
Section: Introductionmentioning
confidence: 99%